2021
DOI: 10.3390/pharmaceutics13040564
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid 3D Printing of Advanced Hydrogel-Based Wound Dressings with Tailorable Properties

Abstract: Despite the extensive utilization of polysaccharide hydrogels in regenerative medicine, current fabrication methods fail to produce mechanically stable scaffolds using only hydrogels. The recently developed hybrid extrusion-based bioprinting process promises to resolve these current issues by facilitating the simultaneous printing of stiff thermoplastic polymers and softer hydrogels at different temperatures. Using layer-by-layer deposition, mechanically advantageous scaffolds can be produced by integrating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 68 publications
0
45
0
Order By: Relevance
“…Furthermore, the localization of alpha and beta cells within the islets was preserved and the printed islets continued to respond to glucose stimulation and produce insulin and glucagon for up to 7 days in culture [165]. In this regard, our group has also contributed to the state of the art by developing 3D-printed polysaccharide-based biomimetic scaffolds (alginate, carboxymethylcellulose and nanofibrillated cellulose) with tailored properties [166]. With the intention of finetuning the 3D printability, rheological, mechanical, swelling, degradation and surface properties of the hydrogels, variable concentrations of NiCu nanoparticles were incorporated into the hydrogels.…”
Section: D Bioprinting Of Biomimetic Scaffoldsmentioning
confidence: 94%
“…Furthermore, the localization of alpha and beta cells within the islets was preserved and the printed islets continued to respond to glucose stimulation and produce insulin and glucagon for up to 7 days in culture [165]. In this regard, our group has also contributed to the state of the art by developing 3D-printed polysaccharide-based biomimetic scaffolds (alginate, carboxymethylcellulose and nanofibrillated cellulose) with tailored properties [166]. With the intention of finetuning the 3D printability, rheological, mechanical, swelling, degradation and surface properties of the hydrogels, variable concentrations of NiCu nanoparticles were incorporated into the hydrogels.…”
Section: D Bioprinting Of Biomimetic Scaffoldsmentioning
confidence: 94%
“…Hydrogel produced from alginate and nanocellulose gives some insight into the advancement in hydrogel properties. A combination of alginate and CMC for wound dressing application can have better ink for printing due to its ability to form gelation and the suitable properties of viscosity and elasticity [ 118 ]. Moreover, the combination can lower the potential of syneresis and provide better mechanical and compression properties for resistance against deformation [ 119 ].…”
Section: Cellulose-based As Biomaterials Inkmentioning
confidence: 99%
“…Mechanical strength values were between those shown by the scaffolds containing pure PCL and pure hydrogels, which could be attributed to their hybrid composition. Besides, the authors suggested that by adjusting the mass ratios of soft polymers and PCL a fine control of the mechanical properties could be provided, being an interesting approach for the development of personalized dressings [97].…”
Section: Algae-derived Biomaterialsmentioning
confidence: 99%